Imperceptible Supercapacitors with High Area‐Specific Capacitance. Issue 24 (12th May 2021) - Ge, Jin; Zhu, Minshen; Eisner, Eric; Yin, Yin; Dong, Haiyun; Karnaushenko, Dmitriy D.; Karnaushenko, Daniil; Zhu, Feng; Ma, Libo; Schmidt, Oliver G
Abstract: Imperceptible electronics will make next‐generation healthcare and biomedical systems thinner, lighter, and more flexible. While other components are thoroughly investigated, imperceptible energy storage devices lag behind because the decrease of thickness impairs the area‐specific energy density. Imperceptible supercapacitors with high area‐specific capacitance based on reduced graphene oxide/polyaniline (RGO/PANI) composite electrodes and polyvinyl alcohol (PVA)/H2 SO4 gel electrolyte are reported. Two strategies to realize a supercapacitor with a total device thickness of 5 µm—including substrate, electrode, and electrolyte—and an area‐specific capacitance of 36 mF cm −2 simultaneously are implemented. First, the void volume of the RGO/PANI electrodes through mechanical compression is reduced, which decreases the thickness by 83% while retaining 89% of the capacitance. Second, the PVA‐to‐H2 SO4 mass ratio is decreased to 1:4.5, which improves the ion conductivity by 5000% compared to the commonly used PVA/H2 SO4 gel. Both advantages enable a 2 µm‐thick gel electrolyte for planar interdigital supercapacitors. The impressive electromechanical stability of the imperceptible supercapacitors by wrinkling the substrate to produce folds with radii of 6 µm or less is demonstrated. The supercapacitors will be meaningful energy storage modules for future self‐powered imperceptible electronics. Abstract : The family of imperceptible electronics still lacks an important member—imperceptible energy storage device with high area‐specific energy density. This study demonstrates imperceptible supercapacitors with 5 µm of total device thickness, 36 mF cm −2 of area‐specific capacitance, and unprecedented electromechanical stability upon bending to radii of 6 µm or less.